The representation and processing of distributivity and collectivity: ambiguity vs. underspecification. Issue 1 (19th January 2021) - Dotlačil, Jakub; Brasoveanu, Adrian
Sentences with plural expressions can receive at least two interpretations. For example, the sentence The boys hold a balloon could mean that the boys as a group jointly hold one balloon (the collective reading) or that each boy holds one balloon, which would imply that as many balloons were held as there are boys (the distributive reading). Building on Frazier et al. (1999 ), we show that the human processor favors collective readings. Crucially, the preference for collective readings is only observed when the distributive reading has to be established through the means of phrasal distributivity (e.g., triggered by distributive quantifiers), and the preference disappears in case of lexical distributivity (e.g., the distributive interpretation of win ). The findings provide evidence for different mental representations of the two types of distributivity and shed light on why the processor exhibits a default preference for collective interpretations.